Preventing and curing problems of heart including angina pectoris, using evolved homeopathy - Biswas, Abhijit; Ramasubramanian , Krishnan (International Journal of Advances in Medicine, 2023)
Heart is one of the most sensitive organs of human body, and is affected by all mental emotions: negative emotions worsen its health, whereas, positive emotions improve its health. This paper presents the methodology of evolved-homeopathy, for preventing and curing problems of heart including angina pectoris, which is considered to be an alarming heart condition in conventional medicine (allopathy) that needs in many of the cases, immediate hospitalization and surgery. The methodology of evolved-homeopathy utilizes a few specific medicines for prevention, according to the first fundamental-principle of cure (‘prevention is better than cure’). For those who are still affected by mild angina due to their tension-ridden lifestyles, a few medicines need to be taken based on the ‘exciting cause’ (which is the third fundamental-principle of cure), to quickly cure, so as to fulfill the second fundamental-principle of cure (‘nipping in the bud’), so that minimum dead-tissue is formed, as revealed by the GDV (gas-discharge-visualization) whole-body diagnostic-chart. Anticipatory preventive doses can be taken whenever felt necessary, as these medicines are complementary type and are having no side effects. Excellent results of prevention, cure and dead-tissue removal using medication, can be achieved by those, who can take quick action based on their own understanding/experience, or on a quick consultation with their doctor. It seems evident that sincere followers of the three fundamental-principles of cure as mentioned above, can counter problems of heart including angina pectoris, and avoid the necessity of hospitalization and surgery.